African Luxury Aesthetics and Politics - Dosekun, Simidele; Iqani, Mehita (Intellect, 2020)
Moving far beyond predominant views of Africa as a place to be 'saved', and even more recent celebratory formulations of it as 'rising', African Luxury: Aesthetics and Politics highlights and critically interrogates the visual and material cultures of lavish and luxurious consumption already present on the continent. Methodologically, conceptually and analytically, the collection dismantles taken-for-granted ideas that the West is the source and focus of high-end and hyper-desirable material cultures. It explores what the culture of consumption means in Africa in both historical and contemporary contexts, studying diverse luxury phenomena including fashion advertising, reality television, retail, gendered consumption and gardening to re-centre the discussion on existing contemporary luxury cultures across the continent.
Description based on print version record.
KU Select 2019: HSS Frontlist Books
Keywords: Political Science / World / African; Business & Economics / Consumer Behavior; Political science; Electronic books